Nurses' and Physicians' Ideas on Initiatives for Effective Use of the Early Warning Score: A Participatory Study - Rikke Rishøj Mølgaard; Lone Jørgensen; Mette Grønkjær; Jacob Østergaard Madsen; Erika Frischknecht Christensen; Siri Lygum Voldbjerg (SAGE Publishing, 2023)
Ineffective use of the early warning score (EWS) can compromise recognition and response to patients' deteriorating condition. This study explores nurses' and physicians' ideas on initiatives for supporting the effective use of the EWS in a hospital setting. Participatory workshops were conducted, and data were analyzed using content analysis. Ideas generated for integrating new functions into the EWS protocol to facilitate effective use are described. Also recommended was that all users receive training and an update on how to use the EWS score to support acceptance and confidence using the protocol and thereby increase adherence to the EWS. Further research is needed on the efficiency of incorporating nurses' clinical judgment in the EWS protocol within different specialties and the effect on adherence to the tool.